Implementation of point‐of‐care ROTEM® into a trauma major haemorrhage protocol: A before and after study. (29th September 2020) - Campbell, Don; Wake, Elizabeth; Walters, Kerin; Ho, Debbie; Keijzers, Gerben; Wullschleger, Martin; Winearls, James
Abstract: Objective: The aim of the present study was to assess transfusion practices with the implementation of a targeted viscoelastic haemostatic assay (VHA) (ROTEM®) guided coagulation management programme into a major haemorrhage protocol for trauma patients requiring ICU admission, starting from time of arrival in the ED. Methods: This retrospective observational study was conducted in a major trauma centre in Australia. One hundred and sixty‐two trauma patients admitted to the ICU between January 2013 and December 2015 with an Injury Severity Score ≥12 and who received blood products were included: 37 in the pre‐group, 48 during implementation and 77 in post‐group. The primary outcome was blood and blood product administration amounts. Results: Packed red blood cell transfusion amounts did not significantly change post introduction of the ROTEM®. There was a significant increase in fibrinogen replacement between the pre‐ and post‐groups ( P  < 0.001), accompanied by a reduction in the use of fresh frozen plasma ( P  < 0.001) and prothrombinex ( P < 0.001). Platelet usage in the post‐group was higher but not reaching statistical significance ( P   = 0.051). Post‐implementation point‐of‐care ROTEM® testing was able to be performed in the ED in 94.8% of cases. Conclusion: Although there was no overall reduction of packed red blood cell usage, a change in the pattern of administration of other blood products was observed with the implementation of a targeted VHA (ROTEM®) guided coagulation management programme. Larger studies are needed to further define the role of early VHA testing to guide correction of trauma‐induced coagulopathy and the effect on clinical outcomes. Abstract : ROTEM® guided blood product replacement in trauma patients results in significant increase in early fibrinogen supplementation and reduction of fresh frozen plasma usage. Larger studies are required to define the exact role and cost benefit of viscoelastic haemostatic assay testing to correct trauma‐induced coagulopathy, and effect on clinical outcomes.